(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Background: Sex estimation plays a critical role in forensic investigations, particularly in cases involving incomplete skeletal remains. While the pelvis and skull are the most sexually dimorphic bones, alternative markers such as the ster num are gaining attention. This study investigates the utility of sternal measurements and the sternal index in determin ing sex and evaluates the applicability of Hyrtl’s Law in forensic contexts. Materials and Methods: A total of 132 cadavers (92 males, 40 females) were examined for sternal morphometry. Parameters measured included total sternal length, manubrium length, and mesosternum length. The sternal index was calculated and analyzed for sexual dimorphism. Additionally, the applicability of Hyrtl’s Law—stating that the manu brium is shorter than the mesosternum—was assessed in both sexes. Results: Males exhibited significantly greater sternal lengths compared to females. The mean sternal index was signifi cantly higher in females, indicating a potential marker for sexual dimorphism. However, notable overlap in sternal index values was observed—98.9% in males and 90% in females—limiting its reliability as a standalone indicator. Hyrtl’s Law was applicable in 71.73% of male cadavers but only in 40% of female cadavers, suggesting limited utility in female sex estimation. Conclusion: The sternum demonstrates measurable sexual dimorphism and may aid in sex estimation when key skeletal elements are unavailable. Although the sternal index and Hyrtl’s Law show potential, their application is constrained by significant overlap between sexes. Further research with larger and more diverse populations is recommended to enhance their forensic reliability.